Studies in law, politics, and society. Vol. 80 - Sarat, Austin (Studies in law, politics, and society ;, 2019)
This volume of Studies in Law, Politics and Society examines the contribution of ethnography to our understanding of contemporary legal and political phenomena, with a particular focus on how it enables us to make sense of modern life under conditions of post-colonialism and globalization.Through the examination of case studies such as affirmative action at the University of Michigan, the US government and tribal consultations, the California Current Large Marine Ecosystem, and freedom of speech on campus, this edited volume demonstrates the value of ethnography as a method of scholarly investigation within law and politics.Written by an impressive group of interdisciplinary scholars, this book will prove invaluable to students and researchers in the fields of law and politics.